Reserving Time for Daddy: The Consequences of Fathers’ Quotas - Patnaik, Ankita (Journal of Labor Economics, 2019)
“Daddy quotas” that reserve some parental leave for fathers are increasingly common in developed nations, but it is unclear whether fathers respond to the binding constraints or the labeling effects they produce. Furthermore, little is known about their long-term effects on household behavior. I examine the Quebec Parental Insurance Plan, which improved compensation and reserved 5 weeks of leave for fathers. I find that fathers’ participation increased by 250%, driven by higher benefits and the framing effect of labeling some weeks as “daddy only.” I also present causal evidence that paternity leave reduces sex specialization long after the leave period.